EDUKASI DALAM MENINGKATKAN KEPATUHAN INTAKE CAIRAN PASIEN PENYAKIT GINJAL KRONIK (PGK) ON HEMODIALISIS - Desak Putu Kurniawati; Ika Yuni Widyawati; Herdina Mariyanti (Universitas Airlangga, 2019)
Introduction: One of the causes of death in patients with chronic kidney disease on hemodialysis was due to the problem of uncontrolled fluid intake. The prevalence at Dr. Soetomo reported hospital as much as 80% increase weight more than 6%. Nursing education in fluid restriction was expected to improve adherence to fluid intake, and therefore contributes to the achievement of the ideal IDGW was less than 2%.Method: Design in this study was pre-experiment. The population in the study were all patients with chronic kidney disease undergoing hemodialysis. The samples obtained were 28 respondents who met to the inclusion and exclusion criteria. Purposive sampling technique was used in this study. The independent variabel was education. The dependent 2 variabel was Inter Dialitic Weight Gain, Qb and systolic blood pressure. Body weight was observered before and after hemodialysis. Blood pressure was observered during hemodialysis. Data were analyzed using Wilcoxon Signed Rank test with significant level of p=0.005.Result: The results showed that IDWG (p=0.157); Qb (p=0.007) and systolic blood pressure (p=0.021). IDWG patients did not undergo significant changes before and after education. Qb and systolic blood pressure of patients experiencing significant changes before and after education. Nursing educations provides significant effect on the patient's fluid intake compliance with indicator Qb and systolic blood pressure.Conclusions: Nursing educations would provide significant effect on compliance if supported by many factors such as family support advocates, social support and motivation of the patients.The provision of education should be carried out continuously and sustainably to obtain optimal results in patients undergoing regular hemodialysis , especially in terms of compliance with hemodialysis therapy and fluid therapy regimen , in order to achieve adequate dialysis. In a subsequent study can be developed not only limited to the provision of education to the patient but also involve the patient's family .